Analisis Konsentrasi Partikulat di Kota Makassar Periode 2019-2023 - Rahim, Husnul Fahma; Sri Suryani (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the concentration of particulate matter, specifically PM2.5 and PM10, in Makassar City during the period from 2019 to 2023. Air quality in Makassar has become a growing concern due to the significant impact of air pollution on public health, especially among vulnerable groups such as children, the elderly, and individuals with chronic illnesses. The method used in this study is a secondary data analysis obtained from the Makassar City Environmental Agency (DLHD). The results show fluctuations in PM2.5 and PM10 concentrations, with a significant decline during the COVID-19 pandemic (2020–2021) and a sharp increase in 2022–2023. The lowest annual average concentration of PM10 was recorded in 2021 at 10.54 µg/m³, while the highest occurred in 2023 at 16.28 µg/m³. For PM2.5, the lowest concentration was recorded in 2021 at 11.05 µg/m³, and the highest in 2023 at 17.83 µg/m³. Seasonal factors such as rainfall, along with economic recovery and the increase in motor vehicle use, are identified as the main contributors to changes in particulate concentrations. These findings highlight the need for more adaptive air pollution control policies.